Ajan Vruksha/ Khandu Chakka (Ehretia Laevis Roxb). Plant Leaves as A Effective Healer in Chronic Varicose Vein Ulcer. – A Case Report - Rushikesh Thakre; Preeti Sujit Borkar; Ketaki Harne; Pradip Tekade (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction— Varicose vein ulcer is caused by abnormal function of veins due to chronic vein insufficiency,vein damage, ageing, obesity, congestive heart failure. Ehretia Laevis Roxb. plant is traditionally used forwounds(1) . Also its efficacy is tested in various wounds except chronic varicose ulcer.(2)The main symptoms of the patient and the important clinical findings:- Patient having swelling, rednessat right foot, yellowish pus discharge, blackness of skin and presence of ulcer since three years with severepain and inability to perform his regular dutiesThe main diagnoses, therapeutics interventions, and outcomes:- Patient having chronic varicosevein ulcer at right leg since three years. Ehretia Laevis Roxb. leaves paste was prepared under all asepticprecaution and daily dressing of Ehretia Laevis Roxb. paste done on wound. Severe pain was reduced within48 hrs after application of paste, which was significant finding. Wound was healed within 40 days withoutany complication and use of antibiotics and pain killerConclusion— Patient was very happy as he got immediate relief from pain and his wound was healedwithout any invasive procedures by application of Ehretia Laevis Roxb. leaves paste.